PENGARUH POSISI DUDUK TERHADAP KELUHAN LOW BACK PAIN PADA MAHASISWA UNIVERSITAS YARSI ANGKATAN 2018 - Milenia, Natasyia (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2023)
Background: Lectures in Indonesia during the COVID-19 pandemic are generally held online, as well as at YARSI University. Sitting for a long time in online lectures requires students to be in a static or even uncomfortable sitting position. Sitting either upright or bent over a period of more than 30 minutes can cause muscle disorders so many individuals experience complaints of low back pain (LBP). It is felt as pain or muscle stiffness under the lower angle of the 12th costae and above the lower gluteal folds (inferior gluteal), with or without pain radiating from the lower back to the legs. The purpose of this study was to determine whether there was a relationship between sitting posture and the incidence of low back pain in YARSI University students class of 2018 from the Faculty of Medicine, Faculty of Law, and Faculty of Information Technology. Methods: The research design used was quantitative analytic with a cross sectional research design. The sample was determined using the simple random sampling method. The collection instrument used in this study was the Oswestry Disability Index (ODI) questionnaire. The researcher analyzed the univariate and bivariate data variables by using the chi-square test. Results: Based on bivariate chi square analysis, the p value of sitting position with complaints of LBP was 0.741 (p>0.05), meaning that there was no significant relationship between sitting position and complaints of LBP. Conclusions: There is no relationship between sitting position and complaints of low back pain on class of 2018 YARSI University students of Faculty of Medicine, Faculty of Law, and Faculty of Information Technology.